A Dual-Type L2 11-88 Peptide from HPV Types 16/18 Formulated in Montanide ISA 720 Induced Strong and Balanced Th1/Th2 Immune Responses, Associated with High Titers of Broad Spectrum Cross-Reactive Antibodies in Vaccinated Mice. (3rd May 2018) - Motavalli Khiavi, Farhad; Arashkia, Arash; Golkar, Majid; Nasimi, Maryam; Roohvand, Farzin; Azadmanesh, Kayhan
Abstract : E. coli -derived concatenated, multitype L2-conserved epitopes of human papillomavirus (HPV) L2 protein might represent a less expensive and pan-type vaccine alternative (compared to type-specific HPV L1 virus-like particles), if stable protein expression and strong immunogenicity features could be met. Herein, three dual-type- (DT-) HPV L2 fusion peptides comprising the three head-to-tail tandem repeats (multimers) of either HPV 16 epitope "17-36" or "69-81" or one copy (monomer) of 11-88 fused to the same residues of HPV 18 were constructed and expressed in E. coli . SDS-PAGE and Western blot analyses indicated the proper expression and stability of the E. coli -derived DT peptides. Mice immunized by formulation of the purified DT peptides and Freund's adjuvant (CFA/IFA) raised neutralizing antibodies (NAbs; the highest for DT: 11-88 peptide) which showed proper cross-reactivity to HPV types: 18, 16, 31, and 45 and efficiently neutralized HPV 18/16 pseudoviruses in vitro . Immunization studies in mice by formulation of the DT: 11-88 × 1 peptide with various adjuvants (alum, MF59, and Montanides ISA 720 and 50) indicated that Montanide adjuvants elicited the highest cross-reactive titers of NAbs and similar levels of IgG1 and IgG2a (switching towards balanced Th1/Th2 responses). The results implied development of low-cost E. coli -derived DT: 11-88 peptide formulated in human compatible ISA 720 adjuvant as a HPV vaccine.